Is conduct after capture training sufficiently stressful? - Wisén, Niclas; Larsson, Gerry; Risling, Mårten; Arborelius, Ulf (Frontiers in Psychology, 2022)
Conduct after capture (CAC) training is for personnel at risk of being captured. To be effective, it needs to be stressful. But how do we know if it is stressful enough? This study uses biomarkers and cognitive measures to evaluate CAC. Soldiers undergoing CAC was measured by the stress hormone cortisol at baseline and during training. Cognitive performance was measured at baseline and after training. Three groups took part Group A (n = 20) was taken after 48 hours of intense tasks leaving them in a poor resting state. Group B (n = 23) was well rested at CAC onset. Group C (n = 10) was part of a survival, evasion, resistance and escape (SERE) instructor course. The CAC training was the same. Group A exhibited a high increase in cortisol during CAC. Compared to baseline, levels were multiple times as high as “expected” values. Group B exhibited elevated levels, slightly lower than those of group A. they also “dropped” to “normal” levels during the latter part of the exercise. Group C displayed least increase, with only slightly elevated levels. Conclusion CAC training is stressful and cortisol levels were elevated enough to satisfy the prerequisite for effective stress inoculation . No cognitive performance drop could be identified, however several participants “froze” during the exercise due to intensive stress.